2004
DOI: 10.1073/pnas.0403519101
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing antibody response during acute and chronic hepatitis C virus infection

Abstract: Little is known about the role of Abs in determining the outcome of hepatitis C virus (HCV) infection. By using infectious retroviral pseudotypes bearing HCV glycoproteins, we measured neutralizing Ab (nAb) responses during acute and chronic HCV infection. In seven acutely infected health care workers, only two developed a nAb response that failed to associate with viral clearance. In contrast, the majority of chronically infected patients had nAbs. To determine the kinetics of strain-specific and crossreactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
332
2
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 375 publications
(365 citation statements)
references
References 34 publications
(25 reference statements)
24
332
2
4
Order By: Relevance
“…HCVpp can be neutralized with antibodies against E2 or immune sera, confirming their dependence on E2 and showing their use in following the kinetics and specificity of the humoral immune response 86,87 . HCVpp infect primary human hepatocytes and a variety of human hepatic cell lines, and their entry is CD81 dependent [88][89][90][91] .…”
Section: Completing the Virus Life Cycle: Extracellular Virionsmentioning
confidence: 75%
“…HCVpp can be neutralized with antibodies against E2 or immune sera, confirming their dependence on E2 and showing their use in following the kinetics and specificity of the humoral immune response 86,87 . HCVpp infect primary human hepatocytes and a variety of human hepatic cell lines, and their entry is CD81 dependent [88][89][90][91] .…”
Section: Completing the Virus Life Cycle: Extracellular Virionsmentioning
confidence: 75%
“…In line with this are studies on the rate of HVR1 evolution that have suggested that the HVR1 region is under immune pressure exerted by neutralizing antibodies (Booth et al, 1998;Kato et al, 1993; Shimizu et al, 1994;Weiner et al, 1992). Nevertheless, by using infectious retroviral pseudotypes, a recent study has shown that neutralizing antibody responses early after infection do not seem to play a role in the resolution of an acute infection (Logvinoff et al, 2004 aspect is that HCV seems to have a wide cell tropism and can infect not only hepatocytes but also cells of the immune system (Bain et al, 2001;Sung et al, 2003). Another important feature is that HCV behaves in infected patients as a complex mixture of genetically distinct but closely related variants, termed quasispecies, which results in a high genetic variability and adaptability (Martell et al, 1992;Mellor et al, 1995;Simmonds, 1995).…”
Section: Introductionmentioning
confidence: 78%
“…The HCVpp panels used to measure neutralizing breadth of plasma samples and mAbs were identical, except that two E1E2 clones used to screen plasma, 1b20 and 1a114, were replaced in mAb experiments by related clones 1b21 and 1a116, which gave more consistent HCVpp infectivity results. HCVpp were produced by lipofectamine-mediated transfection of HCV E1E2 and pNL4-3.Luc.R-E-plasmids into HEK293T cells as previously described (41,42). Neutralization assays were performed as described previously (43).…”
Section: Methodsmentioning
confidence: 99%